Father Melancholy's daughter - Godwin, Gail (Avon Books, 1997)
Father Melancholy's Daughter is widely recognized as one of the author's most poignant and accomplished novels-- a bittersweet and ultimately transcendent story of a young girl's devotion to her father, the rector of a small Virginia church, and of the hope, dreams, and love that sustain them both in the wake of the betrayal and tragedy that diminished their family.